Pengaruh Kualitas Pelayanan, Kualitas Produk, Dan Harga Terhadap Loyalitas Pelanggan “Ada Swalayan” Siliwangi Semarang Melalui Kepuasan Konsumen Sebagai Variabel Intervening - Bachtiar, Dava Tri Agutama; Anomsari, Ariati; Chasanah, Amalia Nur; Farida, Ida (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This research uses a quantitative explanatory survey approach, by distributing questionnaires as a data collection technique. The sampling method used in this research is purposive sampling using the Cochran formula for sampling because the population size is too large and unknown. The research sample consisted of 100 respondents who were consumers of "ADA Supermarket" Siliwangi Semarang. The data analysis technique used is Smart PLS software version 4. The research results show that Service Quality has been proven to have a positive and significant effect on Consumer Satisfaction and customer loyalty. On the other hand, product quality and price do not have a significant effect on consumer satisfaction and customer loyalty. Service Quality can mediate the influence of Customer Loyalty on Consumer Satisfaction, but cannot mediate the influence of Product Quality and Price on Consumer Satisfaction. Keyword: Service Quality, Product Quality, Price, Customer Loyalty, Consumer Satisfaction